NUTRIENT CONTENT OF LITTER BROILER USING LIGNOSELLULOLITIC BACTERIAL - E. B., Sitepu; Sutama, I N. S.; Mudita, I M. (Jurnal Peternakan Tropika; Vol 10 No 3 (2022): Vol. 10 No. 3 Tahun 2022; September - December, 2022)
lignocellulolytic bacteria. The research was conducted from October to November 2021 at the Sesetan Farm and the Laboratory of Animal Nutrition and Forage, Faculty of Animal Husbandry, Udayana University. The design used was a completely randomized design (CRD) consisting of six treatments, namely: fermented litter broiler without lignocellulolytic bacteria as a control (PB0), litter broiler fermented Bacillus substilis BR4LG (PB1), litter broiler fermented Bacillus substilis BR2CL (PB2), fermented litter broiler Aneurinibacillus sp. BT4LS (PB3), fermented litter broiler Bacillus sp. strain BT3CL (PB4), fermented litter broiler Bacillus sp. strain BT8XY (PB5). Each treatment had 4 replications. The variables observed were dry matter DM), organic matter (OM), crude protein (CP), crude fiber (CF), crude fat (EE) and ash. The results showed that the use of lignocellulolytic bacteria was able to increase (P<0.05) crude protein content and crude fat and reduce (P<0.05) crude fiber content of litter broiler, but did not affect the dry matter content, inorganic matter / ash and organic matter (P>0.05). The use of bacterial Bacillus substilis BR4LG (PB1) produced silage with the highest crude protein and lowest crude fiber (P<0.05). Based on the results of the study, it can be concluded that the use of lignocellulolytic bacteria can increase nutrient content, especially crude protein and crude fat, as well as reduce the crude fiber content of litter broiler. Key words: lignocellulolytic bacteria, litter broiler, nutrient content